2020
DOI: 10.32859/era.19.34.1-24
|View full text |Cite
|
Sign up to set email alerts
|

Traditional antidiabetic plants from Indonesia

Abstract: Background: Indonesia with its widely varied geographical features is rich with knowledge and practice in the utilization of plants for maintaining health and treating diseases, including for diabetes mellitus. This review summarizes the result of ethnopharmacological studies mentioning the application of plants to treat diabetes mellitus conducted in Indonesia. Methods:The online literature search using Google Scholar (https://scholar.google.com/) was carried out to collect data on the use of plants for tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…The decrease in blood glucose levels in intervention group was caused by presence of bioactive compounds contained in extract of red betel leaf including flavonoid, alkaloid, tannin, and saponin, while bitter herb extracts contained andrographolid, flavonoid, saponin, phenolic total, and anthraquinone. 21,22,23 As antidiabetic agent, flavonoid and alkaloid are able to regenerate damaged pancreatic beta cells. 8 Red betel leaf extract could reduce blood glucose level in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in blood glucose levels in intervention group was caused by presence of bioactive compounds contained in extract of red betel leaf including flavonoid, alkaloid, tannin, and saponin, while bitter herb extracts contained andrographolid, flavonoid, saponin, phenolic total, and anthraquinone. 21,22,23 As antidiabetic agent, flavonoid and alkaloid are able to regenerate damaged pancreatic beta cells. 8 Red betel leaf extract could reduce blood glucose level in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…crispa has also been used for a long time in particularly Indonesian and Malaysian folk medicine as an ingredient of popular jamus for lowering elevated blood sugar levels [149]. As a result, some products prepared from the leaf of the plant have recently entered the health-food market as antidiabetic nutraceuticals in the form of sachets containing the raw crude powder (fermented and unfermented) for preparing a tea, as an additive in coffee, or as capsules for oral intake [150]. So far, no clinical data are available on the safety and side effects of the long-term use of these products, but several pharmacological studies reported that they do not exert acute toxicity [151,152].…”
Section: Acanthaceae: Strobilanthes Crispa (L) Blumementioning
confidence: 99%
“…Like Indonesians and other peoples from south-eastern Asian countries, Surinamese-Javanese use tea from S. crispa leaves (alone or together with those from certain other plants) to lower elevated blood sugar levels [51]. This traditional use is supported by the blood-glucose-lowering effects of hot water extracts of fermented and/or unfermented leaf in both normal and streptozotocin-induced diabetic rats [150]. Both preparations also improved lipid profile (total cholesterol, triglyceride, LDL-cholesterol, and HDL-cholesterol) in the animals [150].…”
Section: Acanthaceae: Strobilanthes Crispa (L) Blumementioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus is a metabolic disorder disease that occurs chronically and is caused by many factors with characteristics of high blood sugar levels. Hyperglycemia and hyperlipidemia are one of the main characteristics of diabetes mellitus, which can trigger complications (Hartanti & Budipramana, 2020;Pappachan et al, 2019;Salehi et al, 2019). Therefore, efforts to control blood sugar levels are the primary goal to delay the development of complications in patients with diabetes mellitus (Sun et al, 2021;Febrinasari et al, 2020;Maruhashi & Higashi, 2021).…”
Section: Introductionmentioning
confidence: 99%